GAMBARAN KENAIKAN BERAT BADAN AKSEPTOR KONTRASEPSI SUNTIK PROGESTIN - Aibah; Yuni Astuti Anggraini, Tyasning (MEDIA ILMU KESEHATAN, 2015)
Background: Injection contraceptive is mostly used by acceptors in Indonesia, including in Yogyakarta. The acceptors has reached a number of 201.481 (36,54 %), among which the biggest number of users is located in Gunungkidul (49,29 %) and Gedangsari II Prim ary Health Center served the most injection contraceptive acceptors (77,0 %). Preliminary study that was conducted in January 2015 in Gedangsari II Primary Health Center suggested that the side effect of weight gain was the typical problem commonly faced by the acceptors. Objective: To describe the body weight gain on Progestin injection contraceptive acceptors at Gedangsari II Primary Health Center in Gunungkidul in the year of 2014. Method: This study was a descriptive design observational and conducted in Gedangsari II Primary Health Center during 13–15 May 2015. Samples were classified through purposive sampling technique, with a number of 53 samples who met the inclusion criteria. Data were analyzed by applying multi variable analysis. Result: The majority of body weight prior to any use of Progestin injection contraceptive ranged between 50-60 kg on 30 acceptors (56,6 %) with 55,7 kg on average. The majority of body weight in the post use of Progestin injection contraceptive ranged between 50-60 kg on 28 acceptors (52,8 %) with 57,8 kg on average and the majority of body weight gain during the use of Progestin injection contraceptive for a year was <2,3 kg on 33 acceptors (62,3 %) with 2,07 kg on average. Conclusion: The average body weight gain in the post use of progestin injection contraceptive for one year was 2,07 kg or less heavy than the previous study’s estimation. Keywords : Body weight gain, Progestin injection